Framing the global : entry points for research - Kahn, Hilary E., 1966- (Global research studies., 2014)
"Framing the Global explores new and interdisciplinary approaches to the study of global issues. Essays are framed around the entry points or key concepts that have emerged in each contributor's engagement with global studies in the course of empirical research, offering a conceptual toolkit for global research in the 21st century"--